A Mobile Robots Experimental Environment with Event-Based Wireless Communication - José Sánchez; Dictino Chaos; Sebastián Dormido-Canto; Gonzalo Farias; Ernesto Fábregas; María Guinaldo; Sebastián Dormido (Sensors, 2013)
An experimental platform to communicate between a set of mobile robots through a wireless network has been developed. The mobile robots get their position through a camera which performs as sensor. The video images are processed in a PC and a Waspmote card sends the corresponding position to each robot using the ZigBee standard. A distributed control algorithm based on event-triggered communications has been designed and implemented to bring the robots into the desired formation. Each robot communicates to its neighbors only at event times. Furthermore, a simulation tool has been developed to design and perform experiments with the system. An example of usage is presented.